Contributions of organic matter and nutrients via leaf litter in an urban tropical dry forest fragment - Castellanos-Barliza, Jeiner; León-Peláez, Juan Diego; Armenta-Martínez, Rosalba; Barranco-Pérez, Willinton; Caicedo-Ruíz, William (Revista de Biología Tropical, 2018)
The litterfall and decomposition represent the main transfer of organic matter and nutrients from the vegetation to the soil surface and determine positive trajectories in the process of rehabilitating and restoring degraded ecosystems. The aim of this study was to evaluate the contributions of organic materials and nutrients through the characterization of fine litter in an urban dry forest fragment. Litter production was monitored for one year by collecting 29 traps (0.5 m2). To evaluate leaf nutrient resorption, green leaves were collected from 5-10 individuals that represented the dominant tree species. Litter-bags (20 x 20 cm, 2 mm pore) were used for six months to evaluate the decomposition of leaf litter. Annual fine litter production was found to be 8 574 kg ha-1, with the Cordia alba species contributing the most leaf litter (1 134 kg ha-1) and nutrients (N: 6.16; P: 0.21; Ca: 4.72; Mg: 0.47; K: 1.27 kg ha-1). Decomposition rates (k constant) followed the decreasing order: C. alba (k: 4.6) > Machaerium milleflorum (k: 3.5). M. milleflorum and Albizia niopoides presented a pattern of rapid N and P release in the first 30 days, with more than 80 % and 60 % released from M. milleflorum and C. alba, respectively, by the end of the experiment. The litterfall monitoring carried out in this urban dry forest fragment revealed some important aspects of the functioning of an ecosystem as seriously threatened as the tropical dry forest. Rev. Biol. Trop. 66(2): 571-585. Epub 2018 June 01.